2011
DOI: 10.1016/j.fertnstert.2011.07.687
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised study comparing a GnRH-antagonist versus a GnRH-agonist short protocol for ovarian stimulation in patients referred for IVF

Abstract: Objective: To compare two short protocols for ovarian stimulation in IVF cycles using an antagonist and an agonist short protocol. The outcomes studied were dosis rec FSH needed, days of stimulation, number of oocytes retrieved and pregnancy outcome. Methods: A prospective randomised study design. Inclusion criteria: first or second IVF attempt in women younger than 40 years. In the agonist protocol (Suprefact ® ) nasal spray was used. In the antagonist protocol (Orgalutran) ® was started as soon as at least 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For example, a systematic review reported no difference in clinical pregnancy rate and live birth rates with the GnRH antagonist protocol compared with the longacting GnRH agonist protocol; however, the incidence of OHSS was lower in long-acting GnRH agonist protocol [10]. Another study reported equivalent live birth rate with both protocols [11]. The best protocol for IVF is widely debated in the literature and the optimal protocol remains inconclusive because of several confounders including variation in study population, variation in treatment arms apart from agonist and antagonists, and variation in stimulation strategies [1].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a systematic review reported no difference in clinical pregnancy rate and live birth rates with the GnRH antagonist protocol compared with the longacting GnRH agonist protocol; however, the incidence of OHSS was lower in long-acting GnRH agonist protocol [10]. Another study reported equivalent live birth rate with both protocols [11]. The best protocol for IVF is widely debated in the literature and the optimal protocol remains inconclusive because of several confounders including variation in study population, variation in treatment arms apart from agonist and antagonists, and variation in stimulation strategies [1].…”
Section: Introductionmentioning
confidence: 99%
“…Felberbaum et al have compared GnRH antagonist treatments with luteal long and agonist GnRH protocols in the group under 35 years of age, in the first treatment cycle, having only tubal infertility and classical IVF-applied patients which they classified as the ideal patient group and reported similar embryo transfer rates and clinical pregnancy rates in antagonist-applied patients similar to other agonist protocols ( 18 ) . Gordts et al have compared the short agonist protocol with the antagonist protocol and reported similar implantation, ongoing pregnancy and live birth rates, and also similar cycle periods and obtained oocyte rates ( 19 ) .…”
Section: Discussionmentioning
confidence: 90%
“…There are some limitations to our study. Analog and antagonist cycles were evaluated together because there were many publications showing that the success rates in long-agonist or antagonist cycles were similar [12,17]. Chan et al showed that there was no relationship between endometrial thickness and biochemical pregnancy rates, miscarriage rates, and implantation rates [12].…”
Section: Discussionmentioning
confidence: 99%